Dynamic analysis and optimal control of a novel fractional-order 2I2SR rumor spreading model - Ye, Maolin; Li, Jiarong; Jiang, Haijun (Nonlinear Analysis: Modelling and Control, 2023)
In this paper, a novel fractional-order 2I2SR rumor spreading model is investigated. Firstly, the boundedness and uniqueness of solutions are proved. Then the next-generation matrix method is used to calculate the threshold. Furthermore, the stability of rumor-free/spreading equilibrium is discussed based on fractional-order Routh–Hurwitz stability criterion, Lyapunov function method, and invariance principle. Next, the necessary conditions for fractional optimal control are obtained. Finally, some numerical simulations are given to verify the results.
Keywords: fractional order; rumor spreading; stability; optimal control